Land Allocation for Biomass Crops Challenges and Opportunities with Changing Land Use (Springer International Publishing, 2018)
This edited volume establishes a forum for international experts to explore cutting-edge questions associated with the land use and biomass production. Topics include 'do we have enough land, either primary or marginal, to accommodate future production of biomass?', 'how are farming decisions made in response to biomass incentives?', 'is the current bio-mass production socially, economically and environmentally sustainable?', and 'what are the main constraints currently limiting biofuel deployment?' The expansion of biomass production is often at the cost of reduced land availability for food production and losses of areas with ecological functions such as forests and wetlands. This process often involves complex interplay of physical dynamics and human systems that are driven by numerous geographic and socio-economic factors at different scales. Thus, the state-of-the-art research on the land use issues surrounding the biomass production and its environmental impacts is important for informed land management decision making. This book will be of great use to researchers in land use management and biomass-based renewable energy, as well as practitioners.